Interest in church choir singing among Christian teens in Roman Catholic St. Edmund Church Limbang Sarawak / Mary Anne Peter - Peter, Mary Anne (2008)
This study seeks on the interest among all Christian teens in Roman Catholic St.Edmund Church Limbang Sarawak in joining the church choir singing. Other than that, this study discover what are the problems that happened in church choir ministry and what are the best solution to solve the problem in church choir ministry. In seeking greater understanding, this research is a quantitative study and mainly it is involved the choir member in Roman Catholic St. Edmund's choir ministry. The overall findings of the study show that the numbers of students perceptions were saying that they are really interested in joining the church choir singing and they are love to sing. That is why they frequently come and join the church choir singing. The problems in church choir ministry are lack of knowledge in music, transportation problems, no qualified leaders, no support from parents, they are staying in boarding school, bored during choir practice and they have no friends. The best solution to solve the problems by organize more fun activities in church choir ministry.